Study on the effect of ultrasound on oxygen uptake rate (gas-liquid mass transfer) of saccharomyces cerevisae fermentation - Noor Shahira, Saripa (2013)
The study on the effect of ultrasound on oxygen uptake rate (OUR) and gas-liquid mass transfer of S.cerevisae fermentation are reported objectives were focused on the producing ethanol from bioreactor by S.cerevisae fermentation. The main objective of this study was focused on the gas-liquid mass transfer coefficient (kLa) by a various type of solution, for example (water, glucose solution (50g/l) and fermentation broth). The relationship between kLa with an aeration rate and agitation speed were analyzed for ultrasound and without ultrasound application. Study showed that ultrasound at sonication regiment of 15 watts and 10% duty cycle were exposed to give a good relationship between kLa and fermentation. The profiles of OUR in the fermentation of S.cerevisae also reported. An application of ultrasound at power of 15 Watts gives a better improvement of OUR compared to without ultrasound. Ultrasound has a potential to assist an aeration rate and agitation speed of the fermentation.